Kontribusi UNICEF terhadap Upaya Menegakkan Perlindungan Anak di Indonesia - Dewi Astuti Mudji; Ajeng Laras Caharamayang (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2017)
Child protection issues into the main topics on the Convention on the rights of the child (CRC) that are declared by the United Nations (UN) to assert that children have the right to the protection of the various hazards that threaten it. The results of the Convention have been ratified by the Government of Indonesia in 1990 through Presidential Decree RI No. 36 in 1990. As an international organization under the auspices of the UNITED NATIONS dealing with the issue regarding the issue of children in the world, the United Nations Children's Fund (UNICEF) of course address the issue pertaining to the protection of the child. To address the issue of child protection in Indonesia, UNICEF formulated several program with a focus on the key issues of violations, violence and exploitation, as well as the recording of birth. The purpose of this research is to find out how the contribution of UNICEF in child protection, enforcing, find out how child protection in Indonesia and the last know to find out whether the contribution of UNICEF affects the enforcement of child protection in Indonesia.